Do Prison Inmates Cope with Psychological Distress Well: A Qualitative Study Among Prison Inmates in Sri Lanka - M, Amila Suranga; Vidanapathirana, Janaki (Asian Journal of Interdisciplinary Research, 2022)
Psychological distress is more common among the prison population than in the general population. This is due to overcrowding, various forms of violence, lack of privacy, lack of meaningful activity, isolation from social networks, insecurity about future prospects and inadequate health services, especially mental health services, in prisons. A qualitative study was carried out in 2019 among sixteen prison inmates representing all types of prison institutions in Sri Lanka with the aim of identifying coping strategies of psychological distress. Among them, eight prison inmates were having psychological distress. Majority were between 27-56 years of age and were male. The main strategies adopted by the prison inmates were engaging in different activities, positive thinking about the future, discussing matters with others, avoiding the situations leading to distress and engaging in religious activities. Mainly, the prison inmates who are not psychologically distressed had used these strategies compared to the prison inmates with psychological distress. None of the prison inmates had identified the importance of counselling in coping the psychological distress. Prison inmates have not been given training or awareness regarding the concept of psychological distress or regarding the coping strategies of psychological distress within the prison institutions. Therefore, it is important to include awareness sessions and practical sessions on psychological distress and coping strategies to the introductory awareness sessions conducted for the prison inmates at the time of entry to a prison institution.